Osteosarcoma of the Mandible in an Elderly Patient - Isao Hoshi; Ryosuke Abe; Kei Onodera; Yu Ohashi; Tadashi Kawai; Ikuya Miyamoto; Toshimi Chiba; Yasunori Takeda; Hiroyuki Yamada (Case Reports in Dentistry)
Osteosarcoma is a malignant tumor in which the cancerous cells produce an osteoid matrix or mineralized bone. Jaw bones are affected in 6% of all osteosarcomas and are the fourth most common site of origin. Surgical treatment of osteosarcoma in elderly patients is rarely reported. Here, we report successful treatment of osteosarcoma arising in the mandible of a 90-year-old man. The patient was referred to our institution for diagnosis and treatment of an oral lesion. Intraoral examination revealed that a hard mass measuring 35×27 mm was located on the floor of the oral cavity, attached to the bone, and its growth displaced the tongue posteriorly. Therefore, he experienced difficulty in speech and swallowing. Biopsy of the mandibular mass was suspicious for chondrosarcoma. Preoperative examination did not detect critical risks for general anesthesia or surgery. Based on a clinical diagnosis of a malignant bone tumor of the mandible, segmental mandibular resection with reconstruction using a titanium plate was performed. Surgical site infection occurred on postoperative day 12, which was resolved by drainage, local irrigation, and administration of antibiotics. There was no delirium or cardiovascular or pulmonary complications. Surgery resolved the patient’s difficulties in speech and swallowing. There was no evidence of tumor recurrence or metastasis 4 years after surgery. This case showed that it was not necessary to exclude surgical treatment merely because the patient was 90 years old. Indications for surgery should be determined individually to improve the patient’s quality of life.